Industry 4.0 in SMEs across the globe : drivers, barriers, and opportunities - Müller, Julian M.; Kazantsev, Nikolai (CRC Press, 2022)
"Offering a holistic view of Industry 4.0 development, this book uses examples from twelve different countries around the globe. It provides an Industry 4.0 integration model for Small to Medium-Sized Enterprises (SMEs) and presents avenues that can be taken on how Industry 4.0 and related digitalization programs can be better adopted by SMEs. A broad overview of Industry 4.0 in SMEs, covering twelve countries in various national, historical, and geographical settings are provided. It compares firms of similar size and of similar digitalization levels worldwide and includes descriptions and details of what is currently happening with SMEs in order to increase industrial competitiveness globally. The book goes on to describe some of the barriers, drivers along with opportunities for implementation of Industry 4.0 and related digitalization programs. Experiences of Industry 4.0 implementation in SMEs across different parts of the globe are also added to give the reader a more in-depth experience. This book is a great resource for professionals, academics, researchers, and students from Industrial Engineering and Manufacturing as well as Business Management"- Resumé vydavatel